A Study to Assess the Level of Knowledge and Practice of Dietary Pattern and Association Between the Perceived Stress with Body Mass Index Among Adolescent - Dr.Bhuvaneswari P (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Adolescence is a transitional stage of physical and psychological development that generally occurs during the period from puberty to legal adulthood. Adolescence obesity is one of the main factors to predict adulthood obesity. The objective of the study was to assess the BMI and level of Perceived Stress and to correlate the perceived stress with body mass index among adolescent. Cross sectional study was conducted SIMATS at Chennai. The 50 samples selected as study samples by using the purposive sampling technique and who met the inclusion criteria. Self-administer questioner like demographic data, dietary practice, level of perceived stress was collected and BMI were assessed. Collected data were analysed by descriptive and inferential statistics. Among 50 samples 47 (94%) belongs to female gender; 34 (68%) had moderate knowledge and practicing of dietary pattern; 40 (80%) of the samples had a moderate level of perceived stress; 30 (60%) of the samples belonged to the normal weight class in the BMI class. There is a moderately positive correlation between the perceived stress and BMI range among adolescents. There is a moderately positive correlation between the perceived stress and BMI range among adolescents. The results of this study finding revealed that need of educating adolescent students on good dietary habits. The health team workers should consider risk factors like psychological and metabolic conditions along with dietary habits in the management of obesity among university students and to create a healthy lifestyle